Evaluation of Preoperative Amplitude-Integrated Electroencephalography (aEEG) Monitoring for Predicting Long-Term Neurodevelopmental Outcome Among Infants Undergoing Major Surgery in the Neonatal Period. (October 2016) - Mehta, Bhavesh; Hunt, Rodney; Walker, Karen; Badawi, Nadia
The authors aimed to evaluate preoperative amplitude-integrated electroencephalography (aEEG) patterns for predicting neurodevelopmental outcome among infants undergoing major surgery in the neonatal period. They retrospectively reviewed the preoperative aEEG data of 58 neonates who had undergone major neonatal surgery between 2006 and 2008. The authors classified aEEGs using a weighted background score. Neurodevelopmental outcome was assessed at 3 years of age using the Bayley Scales of Toddler and Infant Development III. Over a third of infants (36%) showed an abnormal aEEG background. Seizure activity was identified in 11 (19%) infants. The majority (68%) of infants had developmental delay, with no significant differences between cardiac and other surgery groups. Logistic regression found no statistically significant but some clinically important associations between aEEG background and neurodevelopmental outcome. Comorbidity was associated with worse outcomes. While the predictive utility of aEEG in this population remains unclear, the findings suggest that further research is warranted.